2002
DOI: 10.1515/bc.2002.030
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation in Glucose-Deprived Medium Stimulates Mitochondrial Biogenesis and Oxidative Metabolism in HepG2 Hepatoma Cells

Abstract: In order to test the hypothesis that an imbalance between energy requirement and energy supply regulates mitochondrial genes and ultimately mitochondrial biogenesis, energy supply was challenged in HepG2 cells by withdrawal of glucose from the culture medium, making the cells exclusively dependent on mitochondrial ATP production. Such cells showed a 2-fold increase of cytochrome c oxidase activity, elevated levels of mitochondrial DNA, mitochondrial DNA encoded mRNAs and proteins, as well as the nuclear encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…This phenomenon has been described for human HepG2 hepatoma cells grown in the absence of glucose for up to 96 h. 46 Thus, the cybrids were placed in glucose-free media for 48 h, and their viability was measured by CFDA assay (Fig. 5A).…”
Section: Report Of Pedigreesupporting
confidence: 60%
“…This phenomenon has been described for human HepG2 hepatoma cells grown in the absence of glucose for up to 96 h. 46 Thus, the cybrids were placed in glucose-free media for 48 h, and their viability was measured by CFDA assay (Fig. 5A).…”
Section: Report Of Pedigreesupporting
confidence: 60%
“…Compared with wild-type fibroblasts, CI/CII ratios were decreased in mutant fibroblast, both in transfected and untransfected cells. To make cells more dependent on OXPHOS function, 7,8 fibroblasts were grown in DMEM-no glucose supplemented with galactose (5 mM) and fetal bovine serum 10%. In galactose medium, CI/CII ratios were also decreased in mutant cells, but they were partially recovered in transfected cells (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Differences in the ultra structure of mitochondria (Hoberman, 1975;Springer, 1980), and depletion cellular mitochondrial numbers have been reported in liver carcinogenesis (Cuezva et al, 2002). Also, as discussed above, differences in content and composition of all oxidative phosphorylation complexes (Irwin et al, 1978;Cuezva et al, 2002;Simonnet et al, 2002) respiratory chain activity (Boitier et al, 1995;Rossignol et al, 2004) expression of oxidative phosphorylation genes (Weber et al, 2002) and levels of mitochondrial DNA (Simonnet et al, 2002;Meierhofer et al, 2004;Mambo et al, 2005) were reported relative to normal controls.…”
Section: Mtdna Mutations In Human Cancermentioning
confidence: 96%